Prevalence of periodontal disease and treatment demands based on a German dental survey (DMS IV) - Holtfreter, Birte; Kocher, Thomas; Hoffmann, Thomas; Desvarieux, Moise; Micheelis, Wolfgang (Journal of clinical periodontology, 2010)
Holtfreter B, Kocher T, Hoffmann T, Desvarieux M, Micheelis W. Prevalence of periodontal disease and treatment demands based on a German dental survey (DMS IV). J Clin Periodontol 2010. 37: 211–219. doi: 10.1111/j.1600‐051X.2009.01517.x. Aim: We assessed the prevalence and extent of periodontitis in Germany. Furthermore, region‐ and gender‐specific differences in periodontal disease prevalence were evaluated. Material and Methods: The fourth German Dental Health Survey is a national cross‐sectional survey conducted in 2005. Nine hundred and twenty‐five adults (35–44 years) and 1040 seniors (65–74 years) were examined. The survey comprised social‐ and health‐related interviews and dental examinations. Probing depth (PD) and clinical attachment loss (CAL) were assessed at three sites at 12 index teeth. Results: Prevalence of CAL3 mm was found in 95.0% in adults and 99.2% in seniors with 68.7% and 91.4% of teeth being affected, respectively. PD4 mm was prevalent in 76.9% and 87.7% in both age groups, respectively. According to the CDC definition considering mesiobuccal and distolingual sites, prevalence of periodontitis was 70.9% and 87.4% in both age cohorts, with one‐fourth and one‐half presenting severe forms, respectively. Periodontal prevalence was significantly higher in male subjects and East German subjects. Conclusions: Periodontitis was highly prevalent in German adults. To reduce periodontal burden, treatment of periodontal diseases and continuous maintenance should become an integral part in dental practice. Furthermore, health recommendations should be implemented at the community, professional, and individual level.